2019
DOI: 10.1016/j.pmedr.2019.100824
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable consumption and emotional distress tolerance as potential links between food insecurity and poor physical and mental health among homeless adults

Abstract: Food insecurity is associated with mental health outcomes among adults experiencing homelessness. Different theoretical explanations have emerged to account for the negative health outcomes among vulnerable populations. The neomaterial theoretical perspective suggests that nutritional deficiencies from experiencing food insecurity are related to negative health outcomes. Whereas, the psychosocial theoretical perspective indicates that perceived disadvantages or inability to cope emotionally (i.e. lower distres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
3
9
0
Order By: Relevance
“…Irrespective of these limitations, the current study results provide preliminary evidence suggesting that adults who experience homelessness and have a lower ability to tolerate distress and/or lack social support may be at a higher risk of experiencing depression and PTSD when experiencing urban stressors. This finding is comparable to previous research that suggested lower distress tolerance may be an important indirect factor between a stressor and a health indicator [ 19 , 20 ] and expands it to urban stress and psychological symptomatology. Thus, homeless adults living in an urban setting might benefit from healthy coping strategies and emotional regulation skills.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Irrespective of these limitations, the current study results provide preliminary evidence suggesting that adults who experience homelessness and have a lower ability to tolerate distress and/or lack social support may be at a higher risk of experiencing depression and PTSD when experiencing urban stressors. This finding is comparable to previous research that suggested lower distress tolerance may be an important indirect factor between a stressor and a health indicator [ 19 , 20 ] and expands it to urban stress and psychological symptomatology. Thus, homeless adults living in an urban setting might benefit from healthy coping strategies and emotional regulation skills.…”
Section: Discussionsupporting
confidence: 87%
“…In the limited available research, lower perceived distress tolerance has been identified as a link between sleep problems and stress [ 19 ]. Further, distress tolerance has shown significant indirect effects on the association between food insecurity and physical and mental health among adults who experience homelessness [ 20 ]. Despite the relevance of urban stress to adults who are homeless, research on the association between urban stress and distress tolerance is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Research among domiciled women indicates that they are more likely to be affected by food insecurity than men [44]. However, at least one study conducted among homeless adults indicated equivalent rates of food insecurity between the sexes [45]. Studies on the link between problematic alcohol use and food insecurity among domiciled groups also show conflicting results regarding whether the associations are predominately experienced by men or by women [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Based on research evidence linking alcohol use and food insecurity among domiciled adults [9,10], it was hypothesized that heavy drinking and probable alcohol dependence/abuse would significantly predict food insecurity among adults experiencing homelessness. Based on studies that have displayed equivalent rates of alcohol use problems [7] and food insecurity [45] among men and women who experience homelessness, null moderation results were predicted. Understanding specific behavioral risk factors that predispose the homeless population to food insecurity is important for the success of interventions designed to reduce food insecurity among homeless adults.…”
Section: Introductionmentioning
confidence: 99%
“…An informed consent process occurred prior to participants completing the survey, and participants were compensated with a $20 department store gift card. More detailed data collection methods have been previously described elsewhere (Hernandez et al, 2019). The study was approved by the Institutional Reviews Boards at the authors' institutions.…”
Section: Data and Samplementioning
confidence: 99%